Effects of low temperature stress on ferritin or aldose reductase overexpressing transgenic tobacco plants - Hegedűs, Attila (Acta Biologica Szegediensis, 2002)
The alfalfa ferritin overproducing CaMVF9 transgenic tobacco and the alfalfa aldose reductase overexpressing ALR1/9 line showed higher FyFm ratios than SR1 plants during ROS generating low temperature stress. The chlorophyll content of CaMVF9 and ALR1/9 lines proved to be much more favourable than that of SR1 plants whereas there was no difference in the electrolyte leakage. Activities of all the tested antioxidant enzymes (POD, CAT, APX, GR, GST) in the leaves were significantly higher in CaMVF9 and ALR1/9 lines, the malondialdehyde content was significantly lowered in the transgenic lines. The antioxidant enzyme systems induced through several redox-signalling mechanisms have simultaneously contributed to the greater tolerance Of CaMVF9 and ALR1/9 lines.